The Effect of Financial Ratios on Stock Prices - Galih Mulya Subastyan (Eduvest - Journal of Universal Studies, 2024)
This study aims to provide empirical evidence on the impact of fundamental factors on stock prices. The factors identified in this study include the current ratio, return on assets, debt to equity ratio, earning per share, and price earnings ratio. The study was conducted on 20 manufacturing companies in the basic industry and chemical sector listed on the Indonesia stock exchange during 2019-2021. The purposive sampling method was used to select the sample. The multiple regression model was employed as a statistical testing tool. The study found that return on assets and earning per share have a significant and positive impact on stock prices, consistent with the hypothesis. However, the current ratio, debt Equity ratio, and price earnings ratio do not significantly impact stock prices.